(3GdMbGFb aj GdJaSjQs - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ChdkG hCNQkG aGJMI GdcJGH bjd EfeG Sei aGJMI GdcJGH dCfg aJM Ydjc HaGJMJg s
(3BNQgG (B:s
(3ShQI CQGjJ bhdg GdPjf ge Yf UdGJge SGghf bGd HYVge GdPjf dGjMUQhfgG dGjYdehf Cf GdUdGI ehGUdI Hjf GdYHO hHjf QHge aEPG de jQGYi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(2) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs